Int. J. Adv. Res. Biol. Sci. 2017
DOI: 10.22192/ijarbs.2017.04.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the antioxidant activity of ethanol extract of Cassis alata using FT-IR, HPLC and GC-MS analysis

Abstract: The aim of the present investigation is to screening of phytochemical constituents for its free radical scavenging activity of ethanol extract of Cassia alata leaves. The preliminary screening was carried out by standard chemical method. It evidenced that the presence of phytochemicals such as alkaloids, carbohydrate, phenols, tannins, falvanoids, steroids, protein and sugar in the ethanol extract. Various functional groups like alcohols, phenols, carboxylic acid and nitro groups were associated with the extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…In contrast, the tannins, steroids / terpenoids, and Reducing compounds were not detected. This result is contrary to a team of researchers who indicated the presence of alkaloids, phenols, tannins, flavonoids, saponins, steroids and sugar in the aqueous extract of the leaves of S. alata 26 . The qualitative chemicals are an indication of an antioxidant and anti-inflammatory values of this plant and may be responsible for the traditional uses of S. alata leaves.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, the tannins, steroids / terpenoids, and Reducing compounds were not detected. This result is contrary to a team of researchers who indicated the presence of alkaloids, phenols, tannins, flavonoids, saponins, steroids and sugar in the aqueous extract of the leaves of S. alata 26 . The qualitative chemicals are an indication of an antioxidant and anti-inflammatory values of this plant and may be responsible for the traditional uses of S. alata leaves.…”
Section: Discussioncontrasting
confidence: 99%
“…Previous studies on Cassia alata chemical composition have also shown a wide range of phenolic compounds including kaempferol, rhein, chrysophanol, aloe-emodin and physcion ( Fernand et al, 2008 ). It has demonstrated considerable free radical scavenging effects ( Sujatha & Asokan, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Octadecanoic acid have been reported as anticarcinogen or antitumoral (Hsouna et al, 2011;Gehan et al, 2009). Fatty acid like butyl hexadecanoate, methyl hexadecanoate, and methyl octadecanoate, has antimicrobial activity (Sujatha et al, 2014;Abubakar & Majinda, 2016). Benzenoids like 2-(2-ethylhexoxycarbonyl)benzoic acid ester has been reported as cytotoxic (Krishnan, Mani & Jasmine, 2014).…”
Section: Discussionmentioning
confidence: 99%